Anti-Black Racism in British Popular Music (1880-1920) - John Mullen (Revue Française de Civilisation Britannique)
The rapid expansion of the British Empire in the second half of the XIXth century was accompanied by a rise in the diffusion and the legitimacy of racist ideas in Britain. Intellectuals wrote of the “scientific” differences between the races, and racial hierarchies were generally accepted by educated people. What of the uneducated? Comic books and children’s magazines about the “heroes” of the British Empire certainly did not hesitate to use racist stereotypes abundantly. Popular racism against Black people served to legitimize the imperial project, but for most of this period was little aimed at a visible ethnic minority in Britain. Our article will aim at analysing the racist content of popular music in this period – both that of the extremely popular “minstrel shows”, where white performers disguised themselves as stereotypical black slaves for the purposes of entertainment, and the “coon songs” which were common in the music halls. We will trace the depiction of the Black Other as the mirror image of the Victorian and Edwardian respectable gentleman and lady, and how, while generally denigrated, the Black persona could also be desired or envied.